الزواج العرفي بين الفقه الإسلامي والقانون الإندونيسي - Yuli Yasin (Al-Zahra : Journal for Islamic and Arabic Studies, 2023)
Customary marriages, also known as unregistered marriages, are often misunderstood as unannounced (siri) marriages, even though not all unregistered marriages are siri (secret) in nature. This study aims to explain the nature of unregistered marriage, its difference from the syar'i marriage, official marriage and unannounced marriage. At the same time, this study also adresses that customary marriage, even though it is legal according to Islamic fiqh, is not recommended since it contradicts with the Qur'anic commandment regarding the need of muslim to comply with waliyyul amr or those who hold authority. The customary marriage also may results in mafsadat which can actually be avoided by registering marriages according to government regulations. Meanwhile, under Indonesian legal system, customary marriage has no legal justification, and as a result there is no legal guarantee for married couples. As well, this study confirms that customary marriage ignores the legal existence to women and children who will be born, such practise is not in accordance with the purpose of the marriage itself.